Smilagenin Protects Dopaminergic Neurons in Chronic MPTP/Probenecid—Lesioned Parkinson’s Disease Models - He, Xuan; Yang, Shuangshuang; Zhang, Rui; Hou, Lina; Xu, Jianrong; Hu, Yaer; Xu, Rang; Wang, Hao; Zhang, Yongfang (Frontiers in Cellular Neuroscience, 2019)
Current therapies for Parkinson’s disease (PD) only offer limited symptomatic alleviation but fail to hamper the progress of the disease. Thus, it is imperative to establish new approaches aiming at protecting or reversing neurodegeneration in PD. Recent work elucidates whether smilagenin (abbreviated SMI), a steroidal sapogenin from traditional Chinese medicinal herbs, can take neuroprotective effect on dopaminergic neurons in a chronic model of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) conjuncted with probenecid mice. We reported for the first time that SMI significantly improved the locomotor ability of chronic MPTP/probenecid–lesioned mice. SMI increased the tyrosine hydroxylase (TH) positive and Nissl positive neuron number in the substantia nigra pars compacta (SNpc), augmented striatal DA and its metabolites concentration and elevated striatal dopamine transporter density (DAT). In addition, dopamine receptor D2R not D1R was down-regulated by MPTP/probenecid and slightly raised by SMI prevention. What’s more, we discovered that SMI markedly elevated striatal glial cell line-derived neurotrophic factor (GDNF) and brain-derived neurotrophic factor (BDNF) protein levels in SMI prevented mice. And we found that SMI increased GDNF and BDNF mRNA level by promoting CREB phosphorylation in 1-methyl-4-phenylpyridimium (MPP+) treated SH-SY5Y cells. The results illustrated that SMI could prevent the impairment of dopaminergic neurons in chronic MPTP/probenecid-induced mouse model.